Kinetic Study of the Bioadsorption of Methylene Blue on the Surface of the Biomass Obtained from the Algae D. antarctica - Jhonatan R. Guarín; Juan Carlos Moreno-Pirajan; Liliana Giraldo (Journal of Chemistry)
Currently, there is a great pollution of water by the dyes; due to this, several studies have been carried out to remove these compounds. However, the total elimination of these pollutants from the aquatic effluents has represented a great challenge for the scientific community, for which it is necessary to carry out investigations that allow the purification of water. In this work, we studied the bioadsorption of methylene blue on the surface of the biomass obtained from the algae D. antarctica. This material was characterized by SEM and FTIR. To the data obtained in the biosorption experiments, different models of biosorption and kinetics were applied, finding that the best fit to the obtained data is given by applying the pseudo-second-order models and the Toth model, respectively. It was also determined that the maximum adsorption capacity of MB on the surface of the biomass is 702.9 mg/g, which shows that this material has great properties as a bioadsorbent.